1993
DOI: 10.1177/0887302x9301100302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Buyers' Job Content in Large and Small Retail Firms

Abstract: The purpose of this study was to compare the job content of apparel buyers in large and small retail companies. Data were collected from 100 department store buyers and 153 independent specialty store buyers in four merchandise categories: women's, men's, and children's apparel and other apparel and accessories. The Position Analysis Questionnaire was used to describe the buyer's job content with regard to 64 worker-oriented job elements. Bonferroni paired comparison t-tests were used to adjust for a Type I er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The own-label buyer's role is, therefore, more heavily weighted towards procedures at the pre-delivery stages of product buying than it is for buyers of branded merchandise. Post-production, merchandisers take over the management of the critical path of the merchandise in own-label retailers, whereas department store buyers in previous studies (Chang & Sternquist, 1994;Fiorito & Fairhurst, 1993) and the buyers of branded merchandise in this study continued to monitor and control stock deliveries during this stage. Indeed, the existence of strong working partnerships forged between buyers and merchandisers in the sample and their collaboration in decision-making was a noteworthy finding, which had not emerged to the same extent in previous studies.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The own-label buyer's role is, therefore, more heavily weighted towards procedures at the pre-delivery stages of product buying than it is for buyers of branded merchandise. Post-production, merchandisers take over the management of the critical path of the merchandise in own-label retailers, whereas department store buyers in previous studies (Chang & Sternquist, 1994;Fiorito & Fairhurst, 1993) and the buyers of branded merchandise in this study continued to monitor and control stock deliveries during this stage. Indeed, the existence of strong working partnerships forged between buyers and merchandisers in the sample and their collaboration in decision-making was a noteworthy finding, which had not emerged to the same extent in previous studies.…”
Section: Resultsmentioning
confidence: 88%
“…Chang & Sternquist, 1994;Chung, Sternquist, & Chen, 2006;Fiorito et al, 2010;Fiorito & Fairhurst, 1993;Hutt, 1979). Research into retail buying of own-label products is particularly limited and frequently focuses on purchasing of food products (e.g.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Limited research has been published focusing on apparel retail buyers (e.g., Anthony & Jolly, 1991;Fairhurst & Fiorito, 1990;Fiorito & Fairhurst, 1989;1993;Shim & Kotsiopulos, 1991; Stemquist, Tolbert, & Davis, 1989;Tolbert, Stemquist, & Davis, 1988). For example, both survey research (Fairhurst & Fiorito, 1990;Shim & Kotsiopulos, 1991) and experimental research (Wagner, Ettenson, & Parrish, 1989) have addressed vendor (manufacturer) selection by retail buyers.…”
Section: Related Literaturementioning
confidence: 99%
“…Goodness of fit as indexed by the multiple correlation coefficient (R = .46) may be considered moderate. However, retail buyers tend to be extremely busy and time-pressured, often working with many distractions (Fiorito & Fairhurst, 1993). Furthermore, goodness of fit as indexed by the multiple correlation coefficient (R = .86), may be considered very strong.…”
Section: Satisfaction With Servicesmentioning
confidence: 99%
“…The study confirms results in earlier research in that retail craft buyers are merchandisers responsible for decision making related to controlling and generating income for the business. The majority of craft buyers in this study also had the primary responsibility of selling, which has not been reported in apparel buyer studies (Wagner, Ettenson, & Parrish, 1989;Fiorito & Fairhurst, 1993). An issue in this study is complexity of roles as owner/buyers in small businesses.…”
Section: Job Content Of Buyersmentioning
confidence: 64%